A global assessment of nitrogen and phosphorus generated in the waste streams of domesticated cats and dogs - Nicholas Cowan; Will Brownlie; Samuel Tomlinson; Edward Carnell; Julia Drewer; Ulrike Dragosits; Peter Levy; Bryan M. Spears (Sustainable Environment)
Domesticated livestock and their waste streams are considered a significant source of nitrogen (N) and phosphorus (P) pollution at the global scale; however, the waste generated (excreta) by domesticated cats and dogs, whose global numbers are estimated at 700 million and 900 million, respectively, is not included in any global inventories or models of N and P pollution sources. Based on parameters derived from a variety of literature sources, this study estimates the total global N and P excretion from domestic cats and dogs to be 4.32 (1.27–7.38) Tg N yr−1 and 0.76 (0.31–1.21) Tg P yr−1 which are equivalent to 3.3 (1.0–5.7)% of N and 3.3 (1.3–5.3)% of P waste produced by livestock at a global level. These estimates are in line with the combined mass of the animals (the total mass of cats and dogs is equivalent to 3.6% of the total mass of domesticated mammalian livestock). While there is a severe under reporting of waste streams for cat and dog waste deposition in literature, we infer from our estimates that global emissions of N2O and NH3 from cat and dog waste are in the region of 43 (13–74) Gg N2O–N yr−1 and 864 ± 654 Gg NH3–N, representing an unreported contribution that may exceed 17.7% of the carbon footprint associated with global pet food production (in the form of N2O emissions).